Tempering and Austempering of Double Soaked Medium Manganese Steels - Glover, Alexandra; Speer, John G.; De Moor, Emmanuel (Frontiers in Materials, 2021)
steel was investigated in the present contribution. The double soaking heat treatment is a two step intercritical annealing heat treatment, which generates microstructures of athermal martensite, retained austenite and ferrite when applied to medium manganese steels. Microstructures following double soaking and (aus)tempering contained a combination of retained austenite, athermal or tempered martensite, and blocky or bainitic ferrite. X-ray diffraction, dilatometry and transmission Kikuchi diffraction were utilized to investigate microstructural changes which occurred during tempering or austempering. The resulting mechanical properties were measured using uniaxial tensile testing. The double soaking plus tempering heat treatment was shown to generate an ultimate tensile strength of 1340 MPa in combination with 28 pct total elongation while the double soaking plus austempering heat treatment resulted in an ultimate tensile strength of 1675 MPa and total elongation of 22 pct. Overall, both novel heat treatments produced a combination of strength and ductility desired for the third generation of advanced high strength steels.